2011
DOI: 10.1016/j.scienta.2011.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Performance of peach and plum based rootstocks of different vigour on a late peach cultivar in replant and calcareous conditions

Abstract: 17The field performance of fifteen peach and plum based rootstocks of different vigour 18 (Adesoto, Evrica, Garnem, GF 677, HM-2, Krymsk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
39
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 25 publications
12
39
2
Order By: Relevance
“…Other studies also showed plant mortality in replanting conditions. Remorini et al (2015) registered maximum mortality of 20% and Jiménez et al (2011) of 75% for tested rootstocks.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Other studies also showed plant mortality in replanting conditions. Remorini et al (2015) registered maximum mortality of 20% and Jiménez et al (2011) of 75% for tested rootstocks.…”
Section: Resultsmentioning
confidence: 94%
“…Jiménez et al (2011) evaluated the 'Calrico' peach tree on 15 rootstocks in an area previously cultivated with peach trees for 14 years and found that, in the seventh year, the 'Garnem' and 'PADAC 9907-23' rootstocks exhibited a higher TCSA. In the 'Jesca' peach tree, the 'GF-677' x 'Nemaguard', 'Garnem', 'Monegro', and 'Felinem' interspecific hybrids induced a higher TCSA in an area previously cultivated with peach trees for more than 20 years (Alonso & Espada, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rootstock (R) and cultivar (C) are the factors that have played a significant influence on all the vegetative and yield components [37]. The rootstock × cultivar interaction (R × C) was highly significant for fertility index, yield per tree, yield efficiency and fruit weight parameters (table VIII).…”
Section: Rootstock and Cultivar Interactionmentioning
confidence: 99%